Effect of planting density on morphological characteristics and yield components of soybean (Glycine maxL) cultivars - Kayvan Shamsi; Soheil Kobraee (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
For the purpose of studying the effect of different densities on yield attributes and morphological characteristics in three cultivars of soybean (Glycin max L.), an experiment on research field; Islamic Azad University, kermanshah was performed in 2007-2008. This factorial experiment of research was carried out 3 replication and in the form of the randomize complete blocks design. Cultivars factor were placed in the blocks at 3 levels including M7, M9, and Gorgan3 and density factors at 3 levels including plant were placed on 3, 5, 7 (cm) intra rows spacing in the blocks. The results showed that with increasing density, number of node per plant, number of pod per plant, number of grain per plant and numbers of branches were decreased. The most number of pod per plant and 100 grain weight was observed at the M7 cultiva.The highest number of branches relate to7cm intra rows spacing and the M7 cultivar had highest yield on 3 cm intra row spacing